2004
DOI: 10.1159/000076724
|View full text |Cite
|
Sign up to set email alerts
|

Global Approach to Multichannel Electroencephalogram Analysis for Diagnosis and Clinical Evaluation in Mild Alzheimer’s Disease

Abstract: To establish an early diagnosis of Alzheimer’s disease (AD), we evaluated brain spatial dynamics and cognitive function in mild AD. Seventeen patients with the diagnosis of mild AD and 17 age-matched controls were examined for Ω (global complexity), Σ (total power) and Φ (generalized frequency) by 19-channel electroencephalography (EEG). As a result, the mild AD group showed significantly higher Ω values than the control group. The Φ values were highly correlated with the Mini-Mental State Examination scores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…We report here a low (uncorrected) p-value for the indices N k (p = 0.029; uncorrected) and S k (p = 0.019; uncorrected), and the S-estimator (p = 0.042; uncorrected); however, after post-correction, those effects are not statistically significant. Omega complexity was found to be greater in patients with mild AD, which corresponds to decreased synchronization (Yoshimura et al, 2004). We also observed that effect in our data, but it was weak (p = 0.079; uncorrected).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We report here a low (uncorrected) p-value for the indices N k (p = 0.029; uncorrected) and S k (p = 0.019; uncorrected), and the S-estimator (p = 0.042; uncorrected); however, after post-correction, those effects are not statistically significant. Omega complexity was found to be greater in patients with mild AD, which corresponds to decreased synchronization (Yoshimura et al, 2004). We also observed that effect in our data, but it was weak (p = 0.079; uncorrected).…”
Section: Discussionsupporting
confidence: 72%
“…Omega complexity Ω is a measure derived from principal component analysis (PCA) ) (see (Yoshimura et al, 2004) for an application to EEG). Suppose that we are given n signals X 1 (k), X 2 (k), .…”
Section: Omega Complexity and S-estimatormentioning
confidence: 99%
“…An increase in theta and delta activity and a decrease in alpha and beta activity are commonly observed (Coben et al, 1983(Coben et al, , 1985Giaquinto and Nolfe, 1986;Brenner et al, 1986;Pijnenburg et al, 2004). Furthermore, these abnormalities are correlated with the severity of the disease (Hughes et al, 1989;Kowalski et al, 2001), and a significant correlation has been reported between the generalized frequency value and MMSE scores (Yoshimura et al, 2004). Thus, over the past three decades, the EEG has been found to be a useful tool for detecting, through the extraction of certain features, patients affected by AD and cognitive impairment (Babiloni et al, 2004;Huang et al, 2000;Dierks et al, 1993;Jonkman, 1997;Jeong, 2004;Jung et al, 2007).…”
Section: Functional Neurology 2014; 29(1): 57-65mentioning
confidence: 96%
“…The index S was found to be significantly lower in AD patients [98]. In a related study [110], the index H was significantly lower in MCI and AD patients, however, no such effect was observed for S. Omega complexity was found to be increased in patients with mild AD, which corresponds to decreased synchronization [146]; that effect was also observed in MCI patients [97], but it was non-significant.…”
Section: State Space Synchronymentioning
confidence: 99%